PEMBERDAYAAN IBU RUMAH TANGGA DI DESA KARYA INDAH MELALUI PEMBUATAN CEMILAN SEHAT NUGGET KURKUMIN - Dini Mardhiyani; Eva Oktariani; Denia Pratiwi; Deri Islami (LPPM Universitas Abdurrab, 2023)
This community service activity was carried out with PKK mothers in Karya Indah Village, Kec. Tapung, Kab. Kampar, Riau. Law Number 6 of 2014 article 6 concerning Villages states that village arrangements aim to advance the economy of village communities and overcome national development gaps. The village community without exception includes women in the village of Karya Indah Village, Kec. Tapung, Riau is actually a village potential and asset that can help improve family welfare in particular and improve village welfare in general. The service method is carried out by providing counseling, demonstrations and training. The purpose of this service is expected to solve community problems, namely the low ability of the community in entrepreneurship so that they can contribute to increasing the potential of partners, especially the community by improving the quality of human resources. The level of achievement of the goals of this service program can be said to be successful, which can be seen from the enthusiasm of the participants in participating in the service activities and the ability of the service participants to answer questions after completing the counseling and training provided. The recommendation from this community service activity is that it is necessary to have similar repetitive activities related to training which are related to increasing the potential of the community through training.